2006
DOI: 10.1007/s00125-005-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the relationship between alcohol consumption and coronary heart disease and mortality in type 2 diabetic patients

Abstract: Aims/hypothesis: This systematic review examines the relationship between alcohol consumption and long-term complications of type 2 diabetes. Meta-analyses could only be performed for total mortality, mortality from CHD, and CHD incidence, because the availability of articles on other complications was too limited. Materials and methods: A PubMed search through to September 2005 was performed and the reference lists of relevant articles examined. Among the relevant articles there were six cohort studies report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 38 publications
3
55
1
4
Order By: Relevance
“…The results of our study are consistent with the decreased risk of macrovascular complications with moderate alcohol consumption [3] and suggest that moderate alcohol consumption is associated with a generalised cardiovascular protective effect among diabetes patients. On the other hand, certain studies showed slightly different results for particular microvascular complications.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of our study are consistent with the decreased risk of macrovascular complications with moderate alcohol consumption [3] and suggest that moderate alcohol consumption is associated with a generalised cardiovascular protective effect among diabetes patients. On the other hand, certain studies showed slightly different results for particular microvascular complications.…”
Section: Discussionsupporting
confidence: 88%
“…Of the invited patients, 85% took part in the study. Patients were stratified by sex, age (15-29, 30-44 and 45-60 years) and duration of illness (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), ≥15 years) before ten patients were randomly selected from each stratum. Ethics committee approval was obtained at each centre and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 A meta-analysis of 15 prospective cohort studies showed a J-shaped relation between alcohol consumption and risk of developing diabetes, with a 30% lower risk in moderate alcohol consumers (1 to 2 drinks per day). 12 Two quantitative reviews 73,74 concluded that moderate alcohol consumption was associated with a lower incidence of heart disease or total mortality in patients with type 2 diabetes mellitus. Obviously, the decrease in CVD risk associated with moderate alcohol consumption in hypertensive or diabetic subjects does not reduce the importance of controlling blood pressure or blood glucose, regardless of drinking habits.…”
Section: Alcohol In Hypertensive and Diabetic Patientsmentioning
confidence: 99%
“…In diabetic subjects a meta-analysis of six prospective studies evidenced a close association between moderate alcohol consumption and reduced coronary disease; the reduction of relative risk (RR) was similar in magnitude to that seen in the general population and in hypertensive patients [10].…”
Section: Alcohol and Cvd Diseasementioning
confidence: 99%